Molecular Interaction of Chili Compounds (Capsicum annum L) as a COX-2 Inhibitor - Yohanes Bare; Nurul Imaniyah AHmad; Yohanes Nong Bunga (Mangifera Edu, 2022)
Curly red chili (Capsicum annum L.) is a vegetable that has health benefits. Besides being used as an addictive substance in traditional medicine, Capsicum annum L. is also used for cough treatment, antiseptic, anti-irritant, anti-inflammatory. This research study aims to analyze the physico-chemical and its molecular interactions with COX-2. Capsaicin (CID: 1548943), dihydrocapsaicin (CID: 107982) and homocapsaicin (CID: 6442566) compounds were downloaded from pubchem. While the COX protein (ID: 6cox) from the Protein Data Bank. Molecular interaction and analized by HEX. 8.0.0 and Discovery Studio. The three compounds contained in curly red chilies have unique physico-chemical characteristics. The results of the interaction show that the curly mera chili has a physiological function by inhibiting the performance of COX-2